Sejarah Dan Perkembangan Public Speaking Dalam Komunikasi Dakwah - Weny Maulida Nabila; Silmi Fadhilatunnisa; Meity Suryandari (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
Public speaking or the art of speaking in public has a very important role in Islamic da'wah. These skills are not only needed in everyday life, but also in the world of work. History shows that public speaking has been an integral part of preaching communication since ancient Greece and Rome. In the Islamic context, public speaking is the key to conveying religious messages effectively and influencing the attitudes and actions of communicants. This research is a type of library research with a qualitative approach. Data was collected through reviewing scientific literature, such as books, journals, theses and other sources relevant to the research topic. The research results show that public speaking in Islamic da'wah has a crucial role in spreading religious teachings. History and technological developments show that public speaking is not only an ancient tradition but also continues to adapt to the times. Da'is can utilize modern technology and media to reach a wider audience and strengthen the spread of Islamic values ​​in society. Public speaking has a positive influence in conveying da'wah messages, increasing understanding, motivating and shaping public opinion. The development of technology and modern media has brought a transformation in communication.